Establishing a Relationship of CBR and Base Course Thickness with Base Course Material Properties of different aggregate samples of Nepal - Neupane, Aashma; Khadka, Rajesh (International Journal on Engineering Technology, 2025)
The quality of the construction materials used in pavement layers must be assessed before construction. Some of the important properties governing the suitability and quality of a construction material include California Bearing Ratio (CBR), Los Angeles Abrasion (LAA), Aggregate Impact Value (AIV), and Plasticity Index (PI) value of the material. The base course material must ensure the criteria outlined in the Standard Specifications for Road and Bridge Works published by the Department of Roads. In Nepal, there have not been sufficient studies to establish a relationship between CBR and base course thickness with other physical properties of base course material. Hence, a relationship between LAA, AIV, and PI value of the base material to the CBR value and pavement thickness has been formulated in this study, which can be advantageous in a road construction project to reduce time, acting as an alternative check to design base thickness.